PERAN PENDIDIKAN KEWARGANEGARAAN DALAM PEMBENTUKAN PREFERENSI POLITIK AWAL PEMILIH PEMULA - Muhamad Tarom (LPPM UNSAP & FISIP UNSAP, 2023)
Political preferences are an important aspect for someone to be able to participate well in a democratic system. Based on certain political preferences, a person will have reasons and foundations for their political behavior and choices, including first-time voters. Therefore, understanding aspects of its formation is important to understand their initial understanding before being directly involved in political spaces such as elections. This paper aims to show the important role of citizenship education in influencing the formation of initial political preferences of novice voters. Based on qualitative research conducted in Sumedang City in 2020 on first-time voters who were high school students, it was found that the formation of their initial political preferences was not only influenced by parental preferences as previously believed. They get information regarding their initial views on politics through civics education materials. Information from television and social media related to standards and values in behaving as citizens among other citizens has given them an initial understanding of the importance of participating well in the context of life, including at the start of general elections. This makes citizenship education a space for socialization as well as political education for novice voters. This understanding then becomes one of the basics for developing their understanding of politics and how they should behave as good citizens in a democratic system.